(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Beams that crack are thought to be strengthened faster by using strengthening materials. The purpose of this study is to investigate how Ultra-High-Performance Concrete (R-UHPC), Basalt Fiber Reinforced Polymer (BFRP), and Near Surface Mounted Glass Fiber Reinforced Polymer bar (NSM-GFRP) behave in simply supported strengthened concrete. To complete this study, four beams had to be prepared, cast, and tested. Where one of the beams was adopted as a control beam, and the remaining three beams were strengthened with three different types of strengthen that will be explained later. One of the study’s variables is the strengthening shape or type. To test the specimens, the specific technique applied a two-point load. By talking about the ultimate load, method of failure, cracking development, and load-deflection response, the structural behavior of the specimens was studied. The results of the study illustrated that, in comparison to the control and strengthened specimens, the specimen strengthened with R-UHPC given great increase in ultimate load. Where, the ultimate load is improved by 143% in R-UHPC specimens, 32.5% in BFRP specimens, and 91.01% in NSM-GFRP specimens when strengthening is present. Additionally, strengthened specimens were able to absorb more energy than unstrengthen specimens. Additionally, a numerical analysis using ABAQUS was carried out on the anticipated model that replicated the experimentally tested beams. The load-deflection response and mechanism of failure show that the F.E. model’s results and the laboratory test agreed well.